Rethinking Assessment and Feedback: Adapting Evaluation Methods for the Age of Artificial Intelligence (AI) (Comparative & International Education Series, 2024)
Artificial intelligence (AI) is rapidly transforming the world of higher education, and faculty members play a critical role in enhancing student learning through informed feedback. This chapter explores four key areas related to AI and assessment: 1. The urgency and implications of adopting AI proactively in higher education. 2. Writing comprehensive and adaptable policies to mitigate academic and ethical dilemmas stemming from AI. 3. Reassessing traditional evaluation methods, spotlighting AI's potential to personalize learning and to support the needs of all students. 4. Developing a framework offering recommendations on how to enhance the positive effects and mitigate the negative aspects of AI on assessment and feedback when reviewing student work. By thoughtfully and effectively integrating AI into assessment and feedback, university faculty can harness the technology's potential to improve the educational experience while remaining vigilant against potential pitfalls.                                   Keywords: Assessment, AI Integration, Ethics, Evaluation Techniques, Faculty, Feedback, Higher Education, Neurodiversity